2001
DOI: 10.1111/j.1651-2227.2001.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of publication of the “Practice Parameter for the Management of Hyperbilirubinemia” on treatment of neonatal jaundice

Abstract: The aim of this study was to evaluate the change in the treatment of neonatal jaundice following introduction of the “American Academy of Pediatrics’ Practice Parameter for the management of hyperbilirubinemia in the healthy term newborn'. In a historical control observation cohort study, we examined the rate of phototherapy and exchange transfusions among full‐term (≫37wk gestation) and near‐term (gestational age between 35 and 37 wk and birthweight >2000g) infants in two community hospitals. The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Increased treatment in preterm infants may simply be a spillover effect from the focus on term infants in the 1994 guideline. 10,42 Alternatively, the finding in preterm newborns could be a consequence of the multi-factorial nature of changes in management practice. It is likely that clinical practice changed before the published guideline.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased treatment in preterm infants may simply be a spillover effect from the focus on term infants in the 1994 guideline. 10,42 Alternatively, the finding in preterm newborns could be a consequence of the multi-factorial nature of changes in management practice. It is likely that clinical practice changed before the published guideline.…”
Section: Discussionmentioning
confidence: 92%
“…Only 1 study examined changes in the management of jaundice in relation to the 1994 AAP guideline and found that both phototherapy and exchange transfusion rates declined in 2 community hospitals in Jerusalem. 10 The 1994 guideline and the subsequent 2004 revision raised a number of concerns. The 1994 guideline embraced a "kinder and gentler" approach to the management of jaundice in neonates.…”
mentioning
confidence: 99%
“…15 Studies also showed a decrease in the use of phototherapy and exchange transfusion after the publication of the guideline. 16 This more relaxed approach to jaundice converged with 2 other trends: a push toward early postnatal discharge of term and late preterm infants and initiatives to promote breastfeeding. Our population-based data suggest that these 3 factors had a synergistic effect, ultimately resulting in an overall increase in readmissions for jaundice.…”
Section: Discussionmentioning
confidence: 96%
“…After publishing practical guidelines for the management of hyperbilirubinaemia in healthy term newborns 17, a decrease in PT use has been observed 18. Some authors have discussed this development.…”
Section: Discussionmentioning
confidence: 99%